Classification and Association Analysis of Gerbera (Gerbera hybrida) Flower Color Traits - Zhou, Yiwei; Yin, Mao; Abbas, Farhat; Sun, Yue; Gao, Ting; Yan, Fulong; Li, Xinyue; Yu, Yunyi; Yue, Yuechong; Yu, Rangcai; Fan, Yanping (Frontiers in Plant Science, 2022)
Floral color play crucial role in plant life such as via plant-pollinator interactions and modify the abiotic environment of reproductive structures. In the current study, 123 gerbera accessions were divided into six color groups (white, yellow, orange, pink, red and purple) based on RHSCC calibration and colorimeter measurement. PLS-DA analysis showed that the white group was mainly affected by L* value, a* value, C value, and total anthocyanin content, while the yellow group was positively correlated with L* value, b* value, and total anthocyanin content. Similarly, the orange group was mainly affected by b* value and total carotenoid content, whereas the pink group was positively correlated with L* and h values. Furthermore, the red group was affected by L* value, a* value, C value, and total anthocyanin content, whilst the purple group was mainly distributed by L* value, a* value, b* value, and total anthocyanin content. Based on ‘Jin Xiang’ transcriptome data, 14,106 EST-SSR markers were identified and 48 pairs of primers (19 newly developed primers) were screened. Population genetic structure, NJ clustering, and PCoA analysis showed that 123 gerbera accessions could be divided into two groups. EST-SSR-based association analysis showed that 1, 1, 2, 1, 1, 2, and 1 significant loci were related to L*, a*, b*, C, h, total carotenoid, and total anthocyanin contents, respectively. These results provide an important reference for flower color classification and genetic improvement of gerbera.